Analisis Keberadaan Akun Tiktok @Gerindra dalam Menanggapi Keluhan Masyarakat - Amelia Ramadini; Zakia Salsabila; Nyak Muthia Barokah; Qhiefana Defnusza AR; Fauzi Ihsan Hasibuan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Along with the development of the times, the presence of digital media has provided new choices for politicians and political parties as a medium in political promotion efforts. This is also utilized by the Gerindra Party, with the @Gerindra TikTok account created since 2022. The @Gerindra TikTok account has succeeded in handling public complaints in an innovative and responsive way. The purpose of this study is to see how political communication, public opinion, and media impact people's behavior. The method used is a descriptive method because it explains the problem in the study which contains a description of the incident to describe it systematically. The results of this study show that in the digital era, media is the most effective means of forming public opinion and public participation in the world of politics is also influenced by the process of political communication and public opinion circulating among them.